IMPLEMENTASI NILAI MULTIKULTURAL PADA SANTRI PESANTREN TAHFIDZ QUR’AN MODERN QOMAMADANI BATANG - Hanafi, Nur Muhtadin; Hufron, M. (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2025)
This study aims to examine the implementation of multicultural values among students at the Modern Qomamadani Qur'an Tahfidz Islamic Boarding School in Batang. This research uses a qualitative approach with a case study method. Data were obtained through in-depth interviews, participant observation, and document analysis. The Modern Qomamadani Qur'an Tahfidz Islamic Boarding School in Batang was chosen as the research location because it is known as an institution that integrates religious education with multicultural values. The results of the study indicate that the implementation of multicultural values in this boarding school is carried out through several strategies. First, through a curriculum that integrates materials on tolerance, cultural diversity, and peace. Second, through extracurricular activities that involve students in various activities that emphasize cooperation and appreciation for differences. Third, through everyday practices in the boarding school that reflect respect for the diverse backgrounds of the students. The implementation of these multicultural values has a positive impact on students' attitudes and behavior. Students become more open, tolerant, and able to work with people from various cultural backgrounds. This also strengthens social bonds among students and shapes students' character to be more inclusive and appreciative of diversity. This study concludes that multicultural education in boarding schools plays an important role in shaping students' character to be tolerant and appreciative of differences. The Modern Qomamadani Qur'an Tahfidz Islamic Boarding School in Batang can serve as a model for other religious educational institutions in integrating multicultural values into the educational process.